Effectiveness and safety of repeated percutaneous intervention in an office-based endovascular center in maintaining hemodialysis access. (April 2022) - Patel, Jay; Chang, Stephanie; Manawar, Shaan; Munn, John; Rummel, Mark C; Johnston, Dan; Jain, Krishna
Objectives: Percutaneous dialysis access interventions are routinely used to maintain the patency of dialysis access despite the lack of data regarding their long-term effectiveness. This retrospective study was undertaken to study the effectiveness and safety of percutaneous dialysis access interventions in arm fistulas and bridge grafts in an office-based endovascular center. Methods: Patients who had a percutaneous dialysis access intervention in their upper extremity access site, performed at a single office-based endovascular center over a nine-year period (2007–2016) were included in this study. The patients' demographic factors, patency, and complications were analyzed. Patients were entered in the study after first percutaneous dialysis access intervention. Results: A total of 298 limbs in 259 patients had 913 procedures carried out over a nine-year period. There were 190 access arteriovenous fistulas and 108 arteriovenous grafts. The two most common arteriovenous fistulas were the brachiocephalic fistula ( n  = 74, 39%) and radio cephalic fistula ( n  = 69, 36%). Arteriovenous grafts were most commonly placed in the upper arm ( n  = 66, 61%) followed by the forearm ( n  = 42, 39%). The mean overall patency for all limbs was 50.86 months. Arteriovenous fistulas had a significantly longer patency than arteriovenous grafts (51.65 vs. 42.09 months; P  = 0.01). In addition, patients with two or more percutaneous dialysis access intervention in their arteriovenous fistula had significantly greater patency than those with only one percutaneous dialysis access intervention (58.5 vs. 7.6 months; hazard ratio 0.41; P  = 0.0008). This was not true for the arteriovenous graft group. Women represented 49% of the patient group. Their accesses had shorter patency than men (39.8 vs. 60 months; P  = 0.0007). Conclusions: This data support the use of repeated percutaneous dialysis access intervention to maintain long-term patency of dialysis access sites in an office-based endovascular center. Overall, fistulas have longer patency than grafts and women have poorer outcomes as compared to men